Implementación del sistema SCADA para el control, monitoreo y análisis de indicadores de operación del invernadero del Campus Salache. - Alvarez Pastuña, Jorge Enrique (2020)
The implementation of the SCADA system for the control, monitoring and analysis of operational energy indicators was carried out due to the lack of an automation system in the greenhouse of the Technical University of Cotopaxi of Salache Campus, necessary for the optimal growth of seed and Andean grains. The system is made up of electrical and electronic equipment such as S7 1200 PLC, Sentron PAC 3200 energy analyzer, FC 28 humidity sensors and a type k thermocouple sensor, which allowed the control to be carried out manually and automatically. For the operation remotely, it was carried out through a graphical interface (HMI) for the personnel in charge of the crop. They can perform the different control and monitoring actions according to the behavior of the climatic variables that are presented in the greenhouse, obtaining as a result suitable ranges for the germination of the seeds that are: temperature of 18 to 30 ° C and relative humidity (RH) higher values than 30, average 50 and less than 70%. In addition, it was carried out the evaluation of costs for energy consumption 1 kW / h, water 65 liters per day and fertilizer through the operation indicators management. With the implementation of this system, It was improved the quality and quantity of the Andean seeds and grains during its development because 90% of the total production was obtained.